Loading and triggered release of cargo from hollow spherical gold nanoparticle superstructures1. Issue 93 (11th October 2015) - Zhang, Chen; Brinzer, Thomas; Liu, Chong; Garrett-Roe, Sean; Rosi, Nathaniel L.
<x xml:space="preserve">Abstract</x> Hollow spherical gold nanoparticle superstructures having different average diameters (∼75 nm and ∼150 nm) and near-infrared (NIR) extinction were loaded with the anti-cancer drug, doxorubicin (DOX), and enzyme- and NIR-triggered DOX release were monitored.